A yeast-based screening system identified bakkenolide B contained in Petasites japonicus as an inhibitor of interleukin-2 production in a human T cell line. Issue 10 (12th July 2021) - Uesugi, Shota; Hakozaki, Mayuka; Kanno, Yuko; Takahashi, Honoka; Kudo, Yui; Kimura, Ken-ichi; Yamada, Hidetoshi; Yano, Akira
ABSTRACT: Ca 2+ signaling is related to various diseases such as allergies, diabetes, and cancer. We explored Ca 2+ signaling inhibitors in natural resources using a yeast-based screening method and found bakkenolide B from the flower buds of edible wild plant, Petasites japonicus, using the YNS17 strain ( zds1 Δ erg3 Δ pdr1/3 Δ). Bakkenolide B exhibited growth-restoring activity against the YNS17 strain and induced Li + sensitivity of wild-type yeast cells, suggesting that it inhibits the calcineurin pathway. Additionally, bakkenolide B inhibited interleukin-2 production at gene and protein levels in Jurkat cells, a human T cell line, but not the in vitro phosphatase activity of human recombinant calcineurin, an upstream regulator of interleukin-2 production. Furthermore, bakkenolide A showed weak activity in YNS17 and Jurkat cells compared with bakkenolide B. These findings revealed new biological effects and the structure–activity relationships of bakkenolides contained in P. japonicus as inhibitors of interleukin-2 production in human T cells. Graphical Abstract: